Особенности биотрансформации органических веществ в условиях болотных экосистем Севера(на примере Иласского болотного массива) : PECULIARITIES OF THE BIOTRANSFORMATION OF ORGANIC MATTER UNDER THE CONDITIONS OF NORTHERN MIRE ECOSYSTEMS(BY THE EXAMPLE OF ILASSKOE MIRE MASSIF, RUSSIA) - Селянина С.Б.; Труфанова М.В.; Ярыгина О.Н.; Орлов А.С.; Пономарева Т.И.; Титова К.В.; Зубов И.Н. (Труды Института биологии внутренних вод РАН, 2017)
Рассмотрены изменения свойств торфа и торфяной воды в зависимости от глубины залежи, обсуждён элементный состав торфа и его основных компонентов гуминовых и фульвовых кислот, проанализирован компонентный состав торфа Иласского болотного массива (Архангельская область). На основании полученных данных предложена схема формирования структуры, состава и свойств торфа. Показано, что в процессе торфогенеза в верхних горизонтах происходит быстрое окисление наименее устойчивой части исходных растений пигментов и витаминов, трансформация остальных экстрактивных веществ идёт медленнее, одновременно протекают гидролиз и ассимиляция микроорганизмами легкогидролизуемых соединений. Параллельно формируются новые конденсированные соединения гумус. Разрушение капиллярно-пористой структуры растительного материала, обусловленной его клеточным строением, начинается с некоторым запаздыванием, после окисления сопутствующих и инкрустирующих веществ. В зоне выше уровня промерзания грунтов возможен вынос части гумифицированной массы в прилежащие водотоки. : In this paper, the changes in the properties of peat and peat water are considered depending on the depth of the deposit, the elemental composition of peat and its main components, humic and fulvic acids, is discussed, and the component composition of the Ilasskoe mire (Arkhangelsk Region, Russia) peat is analyzed. Based on the obtained data, a scheme for the formation of structure, composition and properties of peat is proposed. It is demonstrated that in the process of peat bog genesis in the upper horizons, the least stable part of the initial plants pigments and vitamins is rapidly oxidized, the transformation of the remaining extractive substances is slower, and hydrolysis and assimilation of easily hydrolyzable compounds by the microorganisms proceed at the same time. In parallel with that, new condensed compounds, humus, are formed. The destruction of the capillaryporous structure of plant material, due to its cellular structure, begins with some delay, after the oxidation of the accompanying and inlaying substances. At the same time, in the zone above the freezing level of soils, it is possible that a part of the humified mass is transported into adjacent watercourses.